Desenvolvimento de uma ferramenta de scaffolding para criação de código fonte para front-end - Merlin, João Paulo (2018)
Internet has evolved in terms of breadth of access and advancement in terms of improving the features it offers - improved bandwidth and new services. Internet has gone from simply providing static pages to a multimedia interaction platform and business environment. The offered diversity of resources and systems running on Internet make users of web systems more and more demanding, both in terms of data quality and interactivity of systems as well as the existence of new resources. For developers this entails an almost constant search for the learning and use of new technologies and the resources that the languages and their environments offer. For these developers to remain productive it is essential that they can utilize resources that facilitate and accelerate the development and learning of these resources, such as frameworks. The use of web frameworks has increased among developers as it makes development faster and more standardized. In this work we have developed a plugin for generating code from Java classes for the Angular web framework in TypeScript language. The plugin developed beyond converting Java classes into TypeScript code is also capable of generating basic CRUDs based on the created annotations.